Pulmonary Disease Caused by Non-Tuberculous Mycobacteria - Wassilew, Nasstasja; Hoffmann, Harald; Andrejak, Claire; Lange, Christoph (Respiration, 2016)
Non-tuberculous mycobacteria (NTM) include more than 160 ubiquitous, environmental, acid-fast-staining bacterial species, some of which may cause disease in humans. Chronic pulmonary infection is the most common clinical manifestation. Although patients suffering from chronic lung diseases are particularly susceptible to NTM pulmonary disease, many affected patients have no apparent risk factors. Host and pathogen factors leading to NTM pulmonary disease are not well understood and preventive therapies are lacking. NTM isolation and pulmonary disease are reported to rise in frequency in Europe as well as in other parts of the world. Differentiation between contamination, infection, and disease remains challenging. Treatment of NTM pulmonary disease is arduous, lengthy, and costly. Correlations between results of in vitro antibiotic susceptibility testing and clinical treatment outcomes are only evident for the Mycobacterium avium complex, M. kansasii, and some rapidly growing mycobacteria. We describe the epidemiology of NTM pulmonary disease as well as emerging NTM pathogens and their geographical distribution in non-cystic fibrosis patients in Europe. We also review recent innovations for the diagnosis of NTM pulmonary disease, summarize treatment recommendations, and identify future research priorities to improve the management of patients affected by NTM pulmonary disease.